2016
DOI: 10.1039/c5fo00905g
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones and flavonoids of Cassia tora leaves ameliorate sodium selenite induced cataractogenesis in neonatal rats

Abstract: The present study was undertaken to evaluate the efficacy of Cassia tora leaves, an edible plant traditionally used for eye ailments, in preventing experimental cataractogenesis. Cataract is the leading cause of irreversible visual impairment worldwide characterized by the cloudiness or opacification of the lens due to the disturbance of even distribution of lens proteins and lipids. A significant number of epidemiological studies have suggested the potential role of herbal medicine in the prevention of catara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…For HPLC analysis, an ethyl acetate fraction was prepared from HEP as previously described [23] and HPLC analysis was performed using a Prominence Shimadzu High Performance Liquid Chromatograph (Shimadzu) equipped with an injector with a 25 µL loop and a UV detector and a Kinetex C-18 column (250 × 4.6 mm, 5 µm; Phenomenex). The compounds of pomegranate extract were separated at room temperature using a gradient elution program at a flow rate of 0.6 mL/min.…”
Section: Hplc Analysismentioning
confidence: 99%
“…For HPLC analysis, an ethyl acetate fraction was prepared from HEP as previously described [23] and HPLC analysis was performed using a Prominence Shimadzu High Performance Liquid Chromatograph (Shimadzu) equipped with an injector with a 25 µL loop and a UV detector and a Kinetex C-18 column (250 × 4.6 mm, 5 µm; Phenomenex). The compounds of pomegranate extract were separated at room temperature using a gradient elution program at a flow rate of 0.6 mL/min.…”
Section: Hplc Analysismentioning
confidence: 99%
“…Cassia tora leaves delayed the onset and progression of cataract formation in neonatal rats. In addition to preserving the antioxidant defense system, lens morphology and the expression of lens crystallins, Cassia tora attenuated lipid peroxidation, compared to selenite-only treated lenses [235,236].…”
Section: Plant-derived Compounds and Herbal Remediesmentioning
confidence: 96%
“…A total of 238 target genes related to cataracts were identi ed from the OMIM (48), Malacard (8) and Genecard (232), after removing the duplicates. The PPI network (removing nodes without any connection) of these targets were constructed ( Fig.…”
Section: Cataracts Related Target Genesmentioning
confidence: 99%
“…Cassiae semen (CS), the seed of Cassia obtusifolia L. or Cassia tora L. of the family Leguminosae, was initially recorded in the earliest book of Chinese materia medica "Shennong Bencao Jing" and described for treating dizziness and headache, improving vision, and nourishing the liver [7]. Modern pharmacological studies reported the therapeutic potential of Cassia tora leaves in preventing cataract [8,9]. It has been revealed that anthraquinone compounds, including obtusin, emodin, aloe-emodin, are the main bioactive components in CS [10][11][12].…”
Section: Introductionmentioning
confidence: 99%